Impact vs. vision: a critical discourse analysis of Trump and Harris’ leadership rhetoric in the 2024 presidential election - Hamed, Dalia M.; Alqurashi, Naif (Frontiers in Communication, 2025)
IntroductionThis study explores the contrasting rhetorical and leadership styles of Donald Trump and Kamala Harris during the 2024 American Presidential Election, revealing how their discourse strategies reflect societal, economic, and political dynamics.MethodsUsing Norman Fairclough’s Critical Discourse Analysis model (1992), the research examines key campaign speeches to understand how each candidate’s language constructs identities, engages audiences, and addresses voter concerns.ResultsTrump’s “Impact Leadership” employs simplicity, urgency, and emotional resonance, blending fear-based appeals with hopeful messaging to connect with conservatives, moderates, and working-class voters. His focus on nationalism, economic protectionism, and crisis-framing positioned him as a decisive leader. Conversely, Harris’s “Visionary Progressivism” emphasizes inclusivity, systemic reform, and moral appeals, resonating with progressives but lacking the immediacy to mobilize a wider electorate.DiscussionThe study situates these rhetorical styles within the polarized context of economic instability and social fragmentation, contributing to political discourse research by demonstrating how language constructs power and influences voter behavior.